Evolution characteristics of overburden structure in inclined fully mechanized caving under residual coal pillars of the upper layer - LIU Yong; WANG Hongwei; WU Xuesong; TIAN Chengpeng; GUAN Rongfu; NIE Yunxiao; FAN Zhiwei; CAO Peipei (Gong-kuang zidonghua)
In the stratified fully mechanized caving of ultra-thick coal seams, the inclined layout of upper and lower caving faces leads to lower fully mechanized caving face intermittently crossing residual coal pillars of the upper layer. This results in complex overburden breakage and mine pressure behavior, posing challenges to surrounding rock control and hindering safe coal production. Based on the 250203 lower fully mechanized caving face at Yanbei Coal Mine of Gansu Huating Coal Power Co., Ltd., methods of physical similarity simulation experiments, numerical modeling, and field measurements were applied to study the overburden movement and stress distribution evolution characteristics under residual coal pillars of the upper layer during inclined fully mechanized caving. The instability characteristics of residual coal pillars of the upper layer and the variation patterns of surrounding rock support pressure under the disturbance of lower fully mechanized caving were clarified. The overburden of the inclined working face was categorized into internal and external fields, and the evolution characteristics of the overburden structure when the lower fully mechanized caving face crossed the residual coal pillars were revealed. The results showed that the mining of the lower fully mechanized caving face induced instability in residual coal pillars of the upper layer, resulting in large-scale overburden collapse. The roof structure within the disturbed zone evolved progressively into a composite structure of "low-level inverted step cantilever beams and high-level large masonry beams". When the working face was 15 m from the residual coal pillar, the maximum vertical stress of the pillar reached 46.7 MPa, an increase of 9.9% compared to the pre-mining state, with significant pillar deformation observed. When the working face was directly beneath the residual coal pillar, the stress concentration zones of the pillar displayed an approximately crescent-shaped distribution. As the inclined position of the lower fully mechanized caving face relative to the residual coal pillars changed, the overburden breakage in the external field exhibited an approximately symmetrical trapezoidal shape. The dynamic instability of the structure caused the overburden collapse in the internal field to evolve through stages of "asymmetric double arches", "symmetric double arches", and "single arch". These findings provide significant guidance for the safe mining of stratified fully mechanized caving faces in ultra-thick coal seams.